AgriLink: an innovative real-time data monitoring and connectivity platform for an orange orchard in Morocco - Baraka, Kamal; Ezzahar, Jamal; Madiafi, Mohammed; Erraji, Hassan; Vivaldi, Gaetano Alessandro; Tallou, Anas (Frontiers in Sustainable Food Systems, 2025)
Sustainable and digital agriculture, grounded in robust scientific research, is crucial to addressing the challenges related to the water-food-energy Nexus (WFE). Ensuring global food security, particularly for small-scale farms, presents a major challenge for the scientific community in the coming decades. Despite occupying only 12% of agricultural land, small-scale farms are responsible for around 35% of the world’s food production. In this context, digital and smart farming solutions, including low-cost, energy-efficient technologies, offer a promising way forward. Low-power wide-area networks (LPWAN), such as LoRa, Sigfox, and NB-IoT, are particularly well-suited for Internet of Things (IoT)-enabled agriculture due to their affordable deployment, energy efficiency, and optimal transmission range for agricultural applications. In contrast, existing systems—often based on expensive technologies such as artificial intelligence (AI) or satellite imagery—are not suitable for smallholder farmers for several reasons (high costs, technical complexity, and insufficient resolution for small-scale plots). Therefore, this paper introduces a new IoT-based agricultural platform utilizing LoRaWAN technology, designed to provide an affordable and effective solution within the Moroccan agriculture context, suffering from severe water scarcity in the last decades. The platform, called AgriLink, uses sensors to collect data and transmit it to a gateway via LoRaWAN. The data is then processed and transferred to a server using Python, SQLite, and InfluxDB. Once the server confirms the receipt of the data, it is promptly deleted from the gateway. This approach allows farmers to monitor and manage their irrigation and fertilization systems in real-time, enhancing both efficiency and ease of use, while overcoming the limitations of existing systems. The objective of using this platform is primarily to save more water and fertilizers in fruit tree crop orchards, which consequently serve to promote sustainable agriculture.